1981
DOI: 10.1042/cs0600145
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sensory Nerves in the Cardiovascular and Respiratory Changes with Isometric Forearm Exercise in Man

Abstract: 1. To investigate the stimulus to the cardiovascular and respiratory systems during isometric exercise, two patients with sensory neuropathies affecting forearm afferent nerves were studied and their circulatory and respiratory responses compared with those of normal subjects. The contribution of pain to the cardiorespiratory changes was also investigated in normal subjects by using hypnosis to relieve pain during and after isometric exercise. 2. The patients and normal subjects performed fatiguing isometric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
16
0

Year Published

1983
1983
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 8 publications
(11 reference statements)
4
16
0
Order By: Relevance
“…Tallarida, Baldoni, Peruzzi, Raimondi, Massaro & Sangiorgi, 1981;Tallarida, Baldoni, Peruzzi, Raimondi, DiNardo, Massaro, Visigalli, Franconi & Sangiorgi, 1985). In contrast, studies in man have implicated supraspinal mediation (Muza, Lee, Wiley, McDonald & Zechman, 1983) which may operate in combination with reflexogenic drives (Wiley & Lind, 1971Duncan et al 1981).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Tallarida, Baldoni, Peruzzi, Raimondi, Massaro & Sangiorgi, 1981;Tallarida, Baldoni, Peruzzi, Raimondi, DiNardo, Massaro, Visigalli, Franconi & Sangiorgi, 1985). In contrast, studies in man have implicated supraspinal mediation (Muza, Lee, Wiley, McDonald & Zechman, 1983) which may operate in combination with reflexogenic drives (Wiley & Lind, 1971Duncan et al 1981).…”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, our investigation demonstrates that the alveolar hypocapnia found during fatiguing isometric contractions (Whipp & Phillips, 1970;Wiley & Lind, 1971Duncan et al 1981;Poole, Ward & Whipp, 1986) results in a primary respiratory alkalaemia (Figs 1 and 2) as a consequence of the ventilatory response (Table 2 and Fig. 3) occurring at a time when the exercise-generated metabolites are presumably trapped within the contracting muscles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results from some small series suggest that occlusion had no effect, but Duncan et al (1981) suggested that, if the circulation remains occluded following a 40 % contraction to exhaustion, the subject continues to hyperventilate. This suggests that the muscle reflex can sustain increased ventilation in the absence of contraction and without metabolites reaching the chemoreceptors.…”
Section: Alveolar Pco2mentioning
confidence: 99%
“…This is due in part to the temporal and spatial variation of MPF and CF, which might be caused by rotation of motor unit activity. (Duncan et al 1981;Imms & Mehta, 1989). In some subjects ventilation is eucapnic, whereas others hyperventilate and lower arterial Pco..…”
mentioning
confidence: 99%